The Role of Interior Design in Educational Institutions (Al-Academy, 2025)
This research will display the role of interior design in education institutions, showing the relationship between them with highlighting on its importance and its effects. The problem of the study is the lack of attention on the importance of interior design in educational institutions that lead to many interior design omissions that have been applied for many years, which in their turn have numerous effects on the users of the institutions. Furthermore, this research will highlight on the solving approaches to some common interior design challenges that has been applied in educational institutions. As a primary data, info was collected from several people from books, journals, and scholar websites about their opinions of interior design in educational institutions, including the challenges, the approached solutions, and the effects. In addition, an online survey has been made that collected opinions of professors and students as they are the main users of educational institutions to know their opinions on the approached solutions and their reasons behind their response. This research has discovered that the approached solutions have positive effects on the users, especially the teachers and students that will play a huge role in the teacher’s productivity and the student’s academic achievements